Evolution of orthodontic services in the Brazilian Unified Health System: a time series analysis (2011-2022) - Douglas Teixeira da Silva; Nataly Ferreira de Ávila; Leandro Machado Oliveira; Jaqueline Vilela Bulgareli; Luiz Renato Paranhos; Álex Moreira Herval (BMC, 2024)
Abstract Background Although malocclusion is the third most prevalent oral health condition, orthodontics is not part of the minimum list of mandatory specialties to be offered in the Dental Specialty Centers of the Brazilian public health system, but rather as optional. Since the acknowledgment of this field as a part of the Brazilian Unified Health System (SUS), access to orthodontic procedures has become optional by municipal governments. Therefore, this study analyzed the evolution of orthodontic procedure provision within SUS from 2011 to 2022. Methodology We conducted a retrospective observational study of time series analysis trends on the number of orthodontic procedures and municipalities offering them. The presentation of findings followed the recommendations of the Reporting of Studies Conducted using Observational Routinely Collected Data. Secondary data from 2011 to 2022 were collected from the SUS Department of Informatics. Orthodontic procedures were organized by year, region, state, and municipality. The study applied descriptive analyses, and the Prais-Winsten generalized linear regressions for time series analysis. Results The quantity of municipalities offering orthodontic procedures have shown a small increasing during period analyzed (from 128 to 157). Northeast and South macro-regions have increased consistently the municipalities with orthodontic offering. All regions showed stable trends for each procedure, except for the South, which exhibited increasing rates of space maintainer placement (Annual Percentage Change (APC): 72.95; 95% CI: 31.6, 127.3) and maintenance sessions (APC: 15.40; 95% CI: 4.5, 27.5). The study showed decreasing trends for appliance removal in the South (APC: -38.07; 95% CI: -47.1, -27.5) and Northeast (APC: -25.19; 95% CI: -36.5, -11.9) regions. Conclusion From 2011 to 2022, there was a small increase in number of municipalities offering orthodontic procedures in the Brazilian public health system, in addition to a stationary trend for almost all types of procedures.